The Influence of E-Commerce, Accounting Information Systems and Digital Literacy on Students' Entrepreneurial Interest (Financial Literacy as a Moderating Variable) - Purnatasari, Aprelinda; Hidayat, Rendra Arief (PT Aksara Indo Rajawali, 2024)
This research aims to determine the influence of understanding e-commerce, accounting information systems and digital literacy on students' interest in entrepreneurship in East Java with financial literacy as a moderating variable. This research is a development of previous research which provides differences in the addition of financial literacy moderating variable. The selected sample was 100 respondents using the convenience sampling method. This research data was obtained from a questionnaire. Research data was analyzed using multiple regression analysis and moderation using the IBM SPSS 26 Statistics application. The research results showed that there was a simultaneous influence of e-commerce, accounting information systems and digital literacy, but only digital literacy had an independent influence on students' entrepreneurial interest. Apart from that, financial literacy is unable to moderate the influence of e-commerce, accounting information systems and digital literacy on students' entrepreneurial interest. These results emphasize the importance of digital literacy and other factors to increase students' entrepreneurial interest.